Ionic interaction and conductivity of metallic hydrogen - Shvets, V.T.; Savenko, S.V.; Malynovski, Ye.K. (Condensed Matter Physics, 2006)
We calculate the electroresistivity of metallic hydrogen within the framework of perturbation theory in electronproton interaction. To this end we employ the Kubo linear response theory while using the two-time retarded Green functions method to calculate the relaxation time. The expressions for the second and third order contributions are given. To describe the electron subsystem, the random phase approximation is used, allowing for the exchange interactions and correlations in a local field approximation. Thermodynamics of the proton subsystem is assumed to be given by the Percus-Yevick equation. At a given density and temperature the only parameter of the theory is the hard sphere diameter, which is calculated from effective pair ionic interaction. For a completely degenerated electron gas, the latter is determined by the density of the system. The dependence of the second and the third order contributions on the parameters of the theory is investigated. For all densities and temperatures examined here the third order contribution constitutes more than half of the second order term. The corresponding magnitude of resistivity is about 100 ∼ 250µΩ cm.